CLIL activities : a resource for subject and language teachers - Dale, Liz.; Tanner, Rosie (New York ; Cambridge : Cambridge University Press, 2012)
"Innovative activities for Content and Language Integrated Learning (CLIL) teachers and trainee teachers. CLIL Activities is organised into five chapters: Activating, Guiding understanding, Focus on language, Focus on speaking and Focus on writing. A further chapter provides practical ideas for assessment, review and feedback. The Background to CLIL section offers a clear explanation of what CLIL is and its benefits and challenges. The book contains a wide range of easily accessible activities that can be used in any order. Dedicated subject pages include annotated extracts from authentic school teaching materials, demonstrating how language is used in particular school subjects, such as geography, science, maths and ICT. The accompanying CD-ROM contains print-ready CLIL activities"--
Includes bibliographical references (p. 271-273) and index.
Keywords: Language and languages -- Study and teaching; Language arts -- Correlation with content subjects; FOREIGN LANGUAGE STUDY / English as a Second Language